Opini Digital #PERMEDIKBUD30 pada Media Sosial Tiwitter - Rafli Ramadhan; Rian Andika; Wa Ode Sapnano Filanti (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2021)
This paper aims to determine the perception or opinion formed in the community on the hashtag #permendikbud30 on social media twitter. The research method used is mixed methods by combining quantitative methods for statistical calculation of communication networks with a sample of 67 tweet data, 5 actors and 62 relations using netlytic and gephi, with a qualitative method for analyzing text using Digital Movement of Opinion which describes and explains the network. social network and structure. The results of this study show that #permendikbud30 is able to create the ability of netizens' opinions in a communication network with the help of the role of @sumntra_14 popular actor. Another finding is that the Minister of Education and Culture No. 30 of 2021 has support. Warganet gives a new hashtag #supportPermendikbud30.